Characterization of Dipeptide-based Sorbent Materials using Combined Thermodynamic and Inelastic Neutron Scattering Techniques. Issue 1793 (2015) - Paradiso, Daniele; Perelli Cippo, Enrico; Gorini, Giuseppe; Rossi, Giorgio; Larese, J. Z.
ABSTRACT: Using a combination of x-ray diffraction, volumetric adsorption and inelastic neutron scattering (INS) the adsorption properties of methane within the channels of L-Isoleucyl-L-Valine (IV) and L-Valyl-L-Alanine (VA) dipeptides have been investigated. These biomaterials have quasi one-dimensional channels of tunable diameters in the range of 3-6 Å and offer possibilities for selective adsorption, as well as, water and gas transport properties. High-resolution volumetric methane adsorption measurements performed near 100K for IV find that this biomaterial exhibits an adsorption capacity of ∼100 m 2 /g. High-resolution Inelastic Neutron Scattering (INS) measurements were performed at the Spallation Neutron Source using the BASIS spectrometer with ∼ 3.5 μeV resolution. The data clearly indicate that at least two spectral features at energy transfers near 100 and 200 μeV are present, which suggests a lowering of the hindering potential for methane reorientation primarily about the three-fold axis within the IV channels. Such features play a key role in understanding details concerning the potential energy surface. These thermodynamic and INS studies suggest that the flexibility and dynamical motion within the dipeptide channels may play a significant role in the adsorption properties.